The ROOM REDEVELOPMENT TO ENHANCE ROOM QUALITY AND INCREASE OCCUPANCY RATES IN VILLA KAYU RAJA, BALI - Forida Ayu Herini; Oka, I Made Darma; Ni Made Ernawati (UHN IGB Sugriwa Denpasar, 2025)
This research aims to assess the room redevelopment project at Villa Kayu Raja, focusing on enhancing room quality and increasing occupancy rates and design an applicable model for redevelopment projects in similar hospitality setting. The study employs a Project Management Body of Knowledge (PMBOK) based approach (initiating, planning, executing, monitoring and controlling, and closing) supported by theories in Project Success Criteria and Room Occupancy. This study employs a qualitative descriptive approach, the data was collected through observation, in-depth interviews with eight key informants from the Heads of Department (HOD), Focus Group Discussions (FGDs) involving six operational department heads, and comprehensive document studies. The room redevelopment project at Villa Kayu Raja was implemented using the PMBOK process cycle and driven by both internal inputs from the MOD checklist and external guest feedback. The redevelopment significantly improved room quality and the overall guest experience. Key enhancements included modernized furnishings, upgraded bathroom facilities, improved lighting, and the incorporation of aesthetic design elements, all of which contributed to more positive guest perceptions. Operational benefits were also observed, including increased maintenance efficiency, more streamlined housekeeping processes, and a reduction in guest complaints. Occupancy data analysis indicated a notable post project increase of 93.92%, particularly among Free Independent Travellers (FITs), highlighting a strong correlation between room upgrades and market appeal. Furthermore, guest reviews across major Online Travel Agencies (OTAs) reflected higher ratings and frequent mentions of comfort, cleanliness, and interior design as standout features following the redevelopment. These findings support the application of an operational management cycle model in similar redevelopment initiatives. This study contributes and provide practical insights and valuable applied knowledge to the field of hospitality industry, particularly on how strategic room redevelopment projects enhance room quality and increase occupancy rates in similar villa properties.